Heart rate variability and trait anxiety in children with irritable bowel syndrome: is there a link? - M. O. Semen; O. L. Lychkovska; V. D. Semen; O. P. Yelisieieva (Zaporožskij Medicinskij Žurnal)
Aim. The aim of current study was to evaluate parameters of heart rate variability and their correlation with the levels of anxiety in children with irritable bowel syndrome.